2015
DOI: 10.3390/rs8010010
|View full text |Cite
|
Sign up to set email alerts
|

Application of Synthetic NDVI Time Series Blended from Landsat and MODIS Data for Grassland Biomass Estimation

Abstract: Accurate monitoring of grassland biomass at high spatial and temporal resolutions is important for the effective utilization of grasslands in ecological and agricultural applications. However, current remote sensing data cannot simultaneously provide accurate monitoring of vegetation changes with fine temporal and spatial resolutions. We used a data-fusion approach, namely the spatial and temporal adaptive reflectance fusion model (STARFM), to generate synthetic normalized difference vegetation index (NDVI) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 52 publications
3
47
0
2
Order By: Relevance
“…In this stage, although the majority of the oilseed rape pods were green, the proportion of oilseed rape pods was high and the canopy became lager at this stage showing relatively large scattering, which may be due to the rapidly growth of the plant canopy biomass or the uncertainty of measured AGB with respect to tiny gap probabilities of the sampling. Moreover, many previous study have used NDVI time series derived from Landsat and MODIS data for forest and grassland AGB estimation [22,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this stage, although the majority of the oilseed rape pods were green, the proportion of oilseed rape pods was high and the canopy became lager at this stage showing relatively large scattering, which may be due to the rapidly growth of the plant canopy biomass or the uncertainty of measured AGB with respect to tiny gap probabilities of the sampling. Moreover, many previous study have used NDVI time series derived from Landsat and MODIS data for forest and grassland AGB estimation [22,68].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Advanced Very High Resolution Radiometer (AVHRR) (1.1 km spatial resolution at nadir), Moderate-resolution Imaging Spectroradiometer (MODIS) (two bands are imaged at a nominal resolution of 250 m at nadir, five bands at 500 m, and the remaining 29 bands at 1 km), and Landsat TM/ETM+ (30 m spatial resolution) have been used to estimate the canopy condition [22][23][24]. However, in many developing countries, smallholder farming is the main livelihood support for the majority of the population.…”
Section: Introductionmentioning
confidence: 99%
“…It exploits the complementary aspects of data collected by the MODIS and Landsat sensors to produce fused data with Landsat resolution from MODIS imagery [17]. It has been applied and has performed well in several studies of subjects as diverse as public health [18], forest disturbance and regrowth monitoring [19,20], vegetation phenology analysis [21], efforts to improve land cover classification accuracy [22], and estimation of biophysical parameters such as evapotranspiration [23], leaf area index [24], plant biomass [25], and gross primary productivity [26]. STARFM is not restricted to MODIS and Landsat data, but use of other data sources appears to have been rarely reported [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, efforts have been made to merge data properties to obtain images with high spatial and temporal resolutions by using algorithms, such as the spatial and temporal adaptive reflectance fusion model (STARFM) (Zhang et al, 2016), which could support photosynthetic activity evaluations with higher temporal and spatial resolutions that partially maintain the original coarse data. Therefore, based on a method for estimating the growth index at a moderate scale using the Modis database, Xu et al (2013) observed a predominance of areas with stable or balanced growth in temperate grassland development.…”
Section: Resultsmentioning
confidence: 99%